Recent Perspectives on Gene-Microbe Interactions Determining Predisposition to Otitis Media - Mittal, Rahul; Sanchez-Luege, Sebastian V.; Wagner, Shannon M.; Yan, Denise; Liu, Xue Zhong (Frontiers in Genetics, 2019)
A comprehensive understanding about the pathogenesis of otitis media (OM), one of the most common pediatric diseases, has the potential to alleviate a substantial disease burden across the globe. Advancements in genetic and bioinformatic detection methods, as well as a growing interest in the microbiome, has enhanced the capability of researchers to investigate the interplay between host genes, host microbiome, invading bacteria, and resulting OM susceptibility. Early studies deciphering the role of genetics in OM susceptibility assessed the heritability of the phenotype in twin and triplet studies, followed by linkage studies, candidate gene approaches, and genome-wide association studies that have helped in the identification of specific loci. With the advancements in techniques, various chromosomal regions and genes such as FBXO11, TGIF1, FUT2, FNDC1, and others have been implicated in predisposition to OM, yet questions still remain as to whether these implicated genes truly play a causative role in OM and to what extent. Meanwhile, 16S rRNA sequencing, microbial quantitative trait loci (mbQTL), and microbial genome-wide association studies (mGWAS) have mapped the microbiome of upper airways sites and therefore helped in enabling a more detailed study of interactions between host polymorphisms and host microbiome composition. Variants of specific genes conferring increased OM susceptibility, such as A2ML1, have also been shown to influence the microbial composition of the outer and middle ear in patients with OM, suggesting their role as mediators of disease. These interactions appear to impact the colonization of known otopathogens (Streptococcus pneumoniae, Haemophilus influenzae, and Moraxella catarrhalis), as well as Neisseria, Gemella, Porphyromonas, Alloprevotella, and Fusobacterium populations that have also been implicated in OM pathogenesis. Meanwhile, studies demonstrating an increased abundance of Dolosigranulum and Corynebacterium in healthy patients compared to those with OM suggest a protective role for these bacteria, thereby introducing potential avenues for future probiotic treatment. Incorporating insights from these genetic, microbiome, and host-pathogen studies will allow for a more robust, comprehensive understanding of OM pathogenesis that can ultimately facilitate in the development of exciting new treatment modalities.